Chloridizing Volatilization Experiments For Treatment Of Fly Ash Generated In Smelting Furnaces Of Municipal Wastes - Hideyuki Itou (The Minerals, Metals and Materials Society, 2006)
Municipal wastes are mainly incinerated in Japan. Both bottom ash and fly ash from the incineration treatment are smelted recently to decrease the volume. Direct smelting of municipal wastes is also becoming popular. The smelting treatment generates fly ash which contains concentrated heavy metals such as Zn, Pb and Cu, and the harmfulness is causing concern. The smelter fly ash is mainly landfilled after stabilization. An effective treatment process of the smelter fly ash is required to recover the metals. For the treatment process, an application of chloridizing volatilization technique is considered. Chloridizing volatilization experiments were carried out to determine the effects of various factors on the volatilization behaviors in this study. A pretreated ash was mixed with a main raw material which mainly consists of hematite. Calcium chloride water solution was added into the mixture. The mixture was pelletized, dried and used as samples for the volatilization experiments. The sample was placed in the reaction tube heated in an electric resistance furnace. 5%02-95%N2 gas with controlled humidity was introduced into the reaction tube. Effects of humidity in the carrier gas, addition of calcium chloride and mixed ratio of the ash to the main raw material were investigated on the volatilization of Zn, Cu and Pb. To determine the volatilization behavior, samples were taken from the furnace at specified temperatures on the heating stage. In addition, experiments at specified holding temperatures for 15 minutes with shortened heating time were conducted. The two series of experiments revealed the effect of heating temperature on the volatilization behavior of Zn, Cu, Pb and Cl.